RESOLUSI KONFLIK INTERPERSONAL BERBASIS NILAI TEPA SELIRA SEBAGAI KEARIFAN LOKAL JAWA DI SEKOLAH DASAR: KAJIAN PUSTAKA - Muhammad Hash Hashol Haq; Eko Handoyo; Indriani Eko Armaidi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines tepa selira, a Javanese local wisdom, as a strategy for resolving interpersonal conflicts among elementary school students through a thematic literature review approach. Data were collected from 28 peer-reviewed articles sourced from Google Scholar, Garuda, and DOAJ databases, analyzed using thematic analysis across five themes. The findings reveal that interpersonal conflicts in elementary schools are systemic phenomena rooted in low empathy and emotional regulation. Tepa selira, which emphasizes perspective-taking, self-control, and mutual respect, directly addresses these root causes. Compared to other local wisdoms that rely on collective mechanisms, tepa selira operates at the individual level, making it more adaptable for formal educational settings. Implementation can be carried out through subject integration, school culture habituation, activity-based approaches, and guided mediation. This study contributes a culturally-rooted conflict resolution framework applicable to elementary education contexts.